The antimalarial triazine WR99210 and the prodrug PS-15: folate reversal of in vitro activity against Plasmodium falciparum and a non-antifolate mode of action of the prodrug - Kinyanjui, S M; Mberu, E K; Winstanley, P A; Jacobus, D P; Watkins, W M (The American journal of tropical medicine and hygiene, 1999)
We have studied the reversal of activity against Plasmodium falciparum of WR99210, a triazine antimalarial drug, and of the pro-drug PS-15 by folic acid (FA) and folinic acid (FNA). Folic acid and FNA inhibit the growth of P. falciparum in vitro at concentrations > 10(-4.5) and 10(-3.5) mol/L, respectively. The activity of pyrimethamine against Kenyan strains M24 and K39 is reduced 10-12-fold by 10(-5) mol/L of FA, and virtually eliminated by 10(-5) mol/L of FNA. Folates do not antagonise the action of WR99210 against Kenyan strains, and only partially antagonize the action of WR99210 action against the Southeast Asian strains V1/S and W282. Similarly, FA and FNA exerted weak or no antagonism of the action of PS-15. The inability of folates to antagonize the action of WR99210 can be explained in terms of high drug-enzyme affinity, but this does not account for the inability of FA and FNA to antagonize PS-15. These results suggest that action of PS-15 against P. falciparum is primarily due to a non-folate mechanism.